PENGARUH PROGRAM KEPEMILIKAN SAHAM DAN KUALITAS LABA TERHADAP BIAYA EKUITAS - Sartika Wulandari; Widhian Hardiyanti; Bogy Febriatmoko (Faculty of Economic and Business Universitas STIKUBANK, 2016)
The flavor program can align management interests with company owners, in addition it is expected to improve the performance of agents that will be reflected in the quality of corporate profits. Companies that implement the program. Have, employees, management, and executives, with their prisipals. Employees will also enjoy such results. With so risky that the company can continue to be minimized. Investor and creditor confidence will ensure their funds will make the company's capital cost decrease. The data in this study is obtained from the Indonesia Stock Exchange.19 The sample of companies implementing the MCC program during 2008 to 2014. The amount of observation that during that period was 60 observations, this is because the implementation period of each company MCC is different. Testing this research hypothesis using path analysis test using SmartPLS 2.0 M3 software. The empirical results of this study indicate the presence of PKS is also significantly positive and significant to the cost of corporate equity. Profit quality is proxied by significant discretionary accruals and significant to the cost of equity. The MCC does not reflect on the costs to be paid. There is no effect between the cost of the MCC on the cost of the company's capital. Keywords: share ownershop program, profit quality, cos of equity